What Is the Relationship Between Empathy and Mental Health in Preschool Teachers: The Role of Teaching Experience - Huang, Heqing; Liu, Yanchun; Su, Yanjie (Frontiers in Psychology, 2020)
The present study aimed to delineate the characteristics of empathy and mental health in preschool teachers and examine the role of empathy in preschool teachers’ mental health. The sample in this study consisted of 4348 preschool teachers, who were divided into 4 groups according to their years of teaching experience (less than 2 years, 2 to 5 years, 5 to 10 years, and more than 10 years). The Chinese version of the Symptom Checklist 90 was used to measure the mental health symptoms of the participants, and the Chinese version of the Interpersonal Reactivity Index was employed to assess various aspects of the participants’ empathy. The results indicated that preschool teachers scored higher than the controls for most mental symptoms, and most symptoms increased as teaching experience increased, independent of the effect of age. The study also found that the four dimensions of empathy showed different trends across the four teaching experience groups: fantasy remained stable, empathic concerns and perspective taking showed decreasing trends, and personal distress showed an increasing trend. Moreover, the present research found a relatively complex relationship between empathy and mental health in preschool teachers: while fantasy and personal distress positively predicted mental health symptoms in preschool teachers, perspective taking and empathic concern negatively correlated with most of the symptoms. It seems that empathy contains both risky and protective factors for individuals’ mental health, and these factors are affected by years of teaching experience.